THE RELATIONSHIP OF PRODUCT COMPLETENESS AND PRICE WITH PURCHASE DECISION ON MANNA'S NEW HOPE SHOP SOUTH BENGKULU - Jusi Irawan; Karona Cahya Susena; Kaulan (Penerbit Jurnal Indonesia, 2020)
The purpose of this study is to determine a correlation between product completeness and price with purchasing decisions at Toko Harapan Baru in Manna of South Bengkulu. The samples in this study were 120 customers who purchased goods at Toko Harapan Baru Manna of South Bengkulu. Sampling is done by accidental sampling technique. Data collection methods by using questionnaires and analytical methods used are Spearman rank correlation and hypothesis testing. The results showed that product completeness has a very strong correlation with the purchasing decision at Toko Harapan Baru in Manna with a correlation value of 0.888 is located at coefficient interval of 0.80 – 1.000. Then, the value of prices with purchasing decisions of consumer have a strong correlation is 0.787, and lies in the interval coefficient of 0.60 - 0.799. The results of hypothesis testing of correlation between product completeness with purchasing decision shows that the value of t count is greater than t table (20.999 > 1.658), meaning that product completeness has a significant correlation with the purchasing decision at Toko Harapan Baru in Manna of South Bengkulu. The results of hypothesis testing between prices and purchasing decisions indicate that t count is greater than t table (13,850 > 1,658), meaning that the price has a significant correlation with purchasing decisions of consumer at Toko Harapan Baru in Manna of South Bengkulu.